APPROACHES TO DETERMINING AND MEASURING HRM ADDED VALUE - MOSKALENKO, Natalia; POLIETAIEV, Viacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The The article explores approaches to defining the added value of HR management and its evaluation through economic, financial, and social indicators. In the context of globalization and increasing competition in the labor market, human resource management has become one of the key elements for ensuring the sustainable development of organizations. However, to more accurately measure its effectiveness, defining the added value HR functions contribute to the business is necessary. The added value concept in HR management is gaining popularity, primarily through the added value concept formulated by Dave Ulrich. He emphasizes the strategic impact of HR on organizational effectiveness, increasing company value, and enhancing its competitiveness. The article’s primary goal is to summarize existing theoretical approaches to measuring the added value of HR management and to develop methodological recommendations for assessing the current effectiveness of human resource management practices and their strategic contribution to business development. The article examines four key stages in evaluating the added value of HRM, including defining outcome variables, identifying cause-and-effect relationships between HR practices and outcomes, developing appropriate measurement tools, and managing results in the context of achieving the organization’s strategic goals. Special attention is given to four main approaches to assessing the added value of HRM: the Harvard approach, which focuses on organizational effectiveness and stakeholder interests; the financial approach, which focuses on financial results and ROI; the social approach, which considers employee satisfaction and motivation; and the model proposed by Andresen and Novak, which examines both economic and social effects. An important aspect of the evaluation is the use of comprehensive tools, such as internal rate of return, income comparison, work tenure, and training costs, which accurately determine the effectiveness of investments in human capital. The article proposes a comprehensive approach that includes both economic and social factors. In Ulrich’s concept, evaluating the added value of HRM is essential for formulating a human resource management strategy that supports long-term business goals. Creating a system for evaluating added value allows for more precise measurement of HR practices’ contribution to the strategic development of the organization and promotes improved interaction between the HR function and other company departments. The model proposed in the article enables examining the relationship between human resource management, organizational effectiveness, and social outcomes, as well as developing strategies for achieving added value in business.